2013
DOI: 10.2139/ssrn.2403891
|View full text |Cite
|
Sign up to set email alerts
|

A Firm-Level Analysis of ICT Adoption in an Emerging Economy: Evidence from the Colombian Manufacturing Industries

Abstract: This study examines ICT adoption among 3,759 Colombian manufacturing firms, and attempts to identify the factors that are conducive to the adoption and usage of ICT at the firm level. Our major findings are (i) that the adoption of a given information and communication technology is better facilitated when a firm is relatively large, has large human capital, engages in more innovative activities, and when a firm's organizational structure is better aligned with the given technology; (ii) that positive associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 77 publications
1
14
0
5
Order By: Relevance
“…References [14-17] Solar et al [18] have argued that adoption of ICT enhances the quality of learning and improves the quality of education. is is consistent with the study by Gallego et al [19] who argue that, for a successful improvement of the quality of education, a country needs implementation of ICT policies and regulations that must be effective and vigorous at all levels. Babaheidari and Svensson [20] in another study make a different conclusion that the impact of ICT on learning outcomes is not clear.…”
Section: Literature Reviewsupporting
confidence: 91%
“…References [14-17] Solar et al [18] have argued that adoption of ICT enhances the quality of learning and improves the quality of education. is is consistent with the study by Gallego et al [19] who argue that, for a successful improvement of the quality of education, a country needs implementation of ICT policies and regulations that must be effective and vigorous at all levels. Babaheidari and Svensson [20] in another study make a different conclusion that the impact of ICT on learning outcomes is not clear.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Furthermore, Gallego et al (2014) explored the adoption and usage of ICT in manufacturing companies based on a large-scale study in Colombia. Results showed that ICT technology adoption is better facilitated in companies that are relatively large, have large human capital, engage in more innovative activities, and align their organizational structure with the given technology in order to maximize the potential.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They concluded that the most important factors to describe e-business adoption are the industry-specific characteristics and not the country of origin, suggesting that certain industries are more inclined to utilizing e-business tools. Export and innovation-oriented companies are proven to be early ICT adopters as well as e-business adopters, based on a large scale study of Colombian manufacturing companies (Gallego et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, son pocos los estudios que analizan el impacto de las TIC bien sea en el nivel agregado o en el nivel microeconómico. Se pueden mencionar los trabajos de Fedesarrollo (2011) y de Gallego, Gutiérrez, y Lee (2015). El primero se orientó en la estimación del impacto general de las telecomunicaciones sobre el crecimiento económico y utilizaron un panel de 18 países latinoamericanos en el periodo 1980-2010.…”
Section: Introductionunclassified